Effects of open-field warming during grain-filling stage on grain quality of two japonica rice cultivars in lower reaches of Yangtze River delta. (May 2018) - Dou, Zhi; Tang, She; Chen, Wenzhu; Zhang, Haixiang; Li, Ganghua; Liu, Zhenghui; Ding, Chengqiang; Chen, Lin; Wang, Shaohua; Zhang, Hongcheng; Ding, Yanfeng
Abstract: To evaluate the actual and comprehensive response of rice grain quality to global warming in lower reaches of Yangtze River delta, a 3-year open-field warming experiment was conducted with two japonica rice cultivars using Free-air temperature enhancement (FATE) facility. Ningjing3 and Wuyunjing24 were planted under two temperature regimes (NT: natural temperature; ET: elevated temperature) during grain-filling. FATE facility increased rice canopy temperature by 2.7 °C (daytime 1.5 °C/nighttime 3.9 °C), 2.0 °C (daytime 1.6 °C/nighttime 2.5 °C) and 3.4 °C (daytime 2.0 °C/nighttime 4.9 °C) in 2012, 2013 and 2014, respectively. Compared with NT, head rice rate, occurrence of perfect grains, amylose content, setback and consistency were decreased by ET, while occurrence of chalky grains, breakdown, cool paste viscosity, pasting temperature were increased under ET. Response of different chalky types to warming were unstable among cultivars and years. Based on Wu-Gilbert model, we found that the relative activity of starch branching enzyme (SBE) to starch synthase (SS) was decreased by ET, which may contribute to longer average amylopectin chain length. ET increased protein content of rice grain but performed no influence on the relative proportion of amino acids. These results revealed that low-amplitude warming during grain-filling could deteriorate rice milling, appearance and cooking quality, but improved its nutritional quality. Highlights: Low-amplitude open-field warming effects on japonica rice quality were determined. Responses of chalky type occurrence to warming were complex. Warming increased average amylopectin chain length and decreased relative activity of related enzymes. Warming did not affect balance between amino acids.